PENERAPAN HAZARD INDENTIFICATION AND RISK ASSESSMENT (HIRA) PADA APRON DI BANDAR UDARA FATMAWATI SOEKARNO BENGKULU - Ika Endrawijaya; Rayyan Chandra Omardy; Agoes Soebagio (FTK UNSURYA, 2025)
Operational safety in the airside area of airports is a crucial aspect in ensuring smooth and secure flight operations. This study was conducted at Fatmawati Soekarno Airport in Bengkulu with the aim of identifying potential hazards in the apron area and assessing their risk levels using the Hazard Identification and Risk Assessment (HIRA) method. Through direct observation during the On the Job Training program, four safety-related findings were identified: non-compliance with PPE use by ground staff, presence of Foreign Object Debris (FOD), oil spillage on the apron, and aircraft refueling conducted simultaneously with passenger movement. The risk assessment revealed that three findings fell under the unacceptable risk category, while one required risk control. The study recommends mitigation measures based on the hierarchy of hazard control approach for each finding. These results highlight the importance of strengthening safety culture and continuous supervision in apron management to enhance the overall airport safety system